Examining Fraud Tendency: Personal Ethics and Love of Money from a Religious Perspective - Reskino Reskino; Rafrini Amyulianthy; Nadia Tri Silvi (Jurnal Ilmiah Akuntansi, 2024)
This research aims to examine the impact of personal ethics and love of money on fraud tendencies, with religiosity as a moderating variable. This research uses primary data through questionnaires given to accounting and finance staff who work at Islamic commercial banks in the DKI Jakarta area. The research sample consisted of 149 respondents, and the analysis was carried out using the Partial Least Square method (PLS-SEM) using the SmartPLS. The results of this study reveal that love of money has a significant influence on fraud tendencies, while personal ethics does not have a significant influence on fraud tendencies. In addition, religiosity could only moderate the influence of the love of money on fraud tendencies, while no moderation occurred in the relationship between personal ethics and fraud tendencies. The novelty of this research lies in examining the complex relationship between factors such as personal ethics, love of money, religiosity, and fraud tendencies in the context of the Islamic banking environment. The results of this research can provide important insights regarding the factors that influence the tendency of fraud in the banking sector, especially Sharia banking, and the moderating role of religiosity in moderating the impact of the love of money. These findings can provide valuable guidance for Islamic banks and other researchers in their efforts to prevent fraud and develop sustainable business ethics.